The Application of Hotel-Customer Satisfaction Index (H-CSI) Model for International Tourist Hotels in Malaysia - Zhang, Zhifang (2013)
International tourism has an important role in Malaysia, for it has both direct and indirect benefits to host countries (Contour, 2013). In order to gain more benefits from tourism, the government has set tourism goals for both the short and long term. In the short term, the government intends to attract 28 million international travelers in 2014 (News Straits Times, 2013), while in the longer term – by 2020 – they hope to attract 36 million international travelers and increase tourism revenues to above RM168 billion (Kannan, 2013). In order to help the government achieve its goals on tourism, and specifically to help international tourist hotels (ITHs) to increase customer satisfaction levels, this study applied the hotel-customer satisfaction index (H-CSI) model developed by Deng, Yeh and Sung (2013). The aims were to test the applicability of this model in Malaysia and hopefully to help hotel managers in ITHs in Malaysia to manage customer satisfaction better. Three hundred and twenty six ITH customers were surveyed in this research. The results show that the H-CSI model is indeed also applicable in Malaysia. Therefore, this model could help the hospitality industry to improve customer satisfaction and at the same time the government to achieve its goals. However, although this study showed that the H-CSI model can be applied in Malaysia, the results differed in places from those obtained in the original H-CSI model. Consequently, it is recommended that hotel managers adapt the model to their own specific culture and situation, rather than copying it wholesale from other countries. Mediation effects in the H-CSI model were also employed in this research. It is hoped that these results will help future researchers or users have a deeper understanding of this model and how to use it.